The Potencial of Bamboo Shoot for Health - Yenni Okfrianti; Catur Herison; Fahrurrozi Fahrurrozi; Budiyanto Budiyanto (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Bamboo is naturel mixture because it can survive in many habitats and belongs to the order of angiosperms monocots. There are around 1200 – 1500 species of bamboo in the world that grow in hilly areas but do not grow in alkaline, desert and rice fields. Bamboo shoots can be processed into food and even herbal and traditional medicines. Bamboo shoots are a sourece of fiber that can be used as a nutraceutical. Bamboo shoots contain as much as 2.23 – 4.20 gfiber in 100 wet weights in the form of flour, thin slices and capsules. Dendrocalamus asper bamboo shoot flour, Bambusa tuldoides and Bambusa vulgaris with air content < 10 g /100, protein, lipid and ash content< 3 g /100 g and can obtain mineral content > 60 g /100g. Bamboo shoots are a good source of dietary fiber. This review supports the increasing benefits of bamboo shoots in the supports the increasing benefit in the health world to prevent an increase in blood sugar, as antihypertention, and antihyperuresemia. Bamboo shoots can be processed into fermented products containing Lactid Acid Bacteria (BAL) which are beneficial for intestinal microflora which are recommended as probiotics.